Pengaruh Gaya Kepemimpinan, Disiplin Kerja dan Prinsip-Prinsip Good Corporate Governace Terhadap Kinerja Karyawan Supermarket Pamella di Kota Yogyakarta - Satria Luthfi Maulana; Agus Siswanto; Aftoni Susanto (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This study aims to determine leadership style, work discipline and good corporate governance principles on employee performance at the Pamella supermarket in the city of Yogyakarta. The sample used in this study was 130 respondents using a questionnaire. Technical analysis in this study using hypothesis testing, descriptive analysis and multiple linear regression analysis. The results of this study are leadership style, transparency, independence and fairness do not significantly influence the performance of employees at Pamella Supermarket in the city of Yogyakarta. As for the variables of Work Discipline, Accountability and Responsibility have a significant effect on employee performance at the Pamella Supermarket in the City of Yogyakarta. Furthermore, the results of the Fcount test obtained a value of 2,782 and a significance value of 0.010. R Square value of 0.138.